THE ROLE OF EARNED VALUE MANAGEMENT IN DRIVING COST AND SCHEDULE PERFORMANCE IN ENGINEERING PROJECTS - Chauhan, Neeraj (International Journal of Research -GRANTHAALAYAH, 2025)
Earned Value Management (EVM) project management technique is widely recognized and aims at the evaluation of cost, time, and scope of engineering projects’ general progress. This paper focuses on the importance of the Earned Value Management in improving cost and schedule performance, however, stressing on the potentiality in terms of predicting the results of project and the ways to manage it. This paper focuses on what is referred to as ‘Performance Measurement Baseline – Planned Value (PV), Earned Value (EV) and Actual Cost (AC). It also depicts how the application of these instruments will enable project managers to base their decisions on facts, increase efficiency in the rationing of resources and decrease project risks. The study also gives the details of challenges or limitations that architects face when implementing EVM in engineering interventions and ways of addressing such issues. The present work underscores the importance of EVM for project management stressing the ways in which this instrument can improve project performance and overcome time and cost constraints.